Utilization of GIS and Information Technology in Optimizing the Location of Durian Peel Raw Materials for Environmentally Friendly Architecture-Based Industries - Andrew Stefano; Sri Endayani (Jurnal Loupe, 2024)
Durian peel is one of the agricultural wastes that has great potential to be processed into high-value products. However, its utilization is still not optimal due to the lack of information about the strategic location of this raw material. This article aims to discuss the use of Geographic Information System (GIS) and IT technology in identifying the optimal location of durian peel raw materials. GIS is a very effective tool for collecting, managing, and analyzing spatial data related to the location of raw materials, making it easier to determine strategic points for durian shell collection. Architectural design that considers aspects of sustainability, energy efficiency, and minimizing environmental impact, treatment facilities can operate more efficiently and environmentally friendly. Industrial engineering also plays an important role in improving the efficiency of the processing process. By applying the right industrial techniques, the production process can be optimized to produce high-value products at a lower cost. The use of GIS and IT technology, coupled with the principles of environmentally friendly architecture and industrial engineering, can provide a comprehensive solution to optimize the use of durian peel as a raw material for high-value products.